2022
DOI: 10.1007/s11011-022-00918-5
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-185 is a common pathogenic event in 22q11.2 deletion syndrome-related and idiopathic schizophrenia

Abstract: M. (2022). Downregulation of miR-185 is a common pathogenic event in 22q11.2 deletion syndrome-related and idiopathic schizophrenia. Metabolic Brain Disease, 37(4),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In the past few years, a considerable amount of research has been conducted to examine the role of miRNAs in neuropsychiatric disease [147][148][149][150][151][152][153][154][155][156]. We and other investigators have examined the expression of miRNAs in human postmortem brains of depressed subjects, in the brain of animals showing depression-like behavior, and in peripheral tissues such as blood, urine, and saliva [6,96,144,150,[157][158][159][160][161][162][163][164][165][166][167].…”
Section: Studies Of Dna Methylation In Adolescents With Elsmentioning
confidence: 99%
“…In the past few years, a considerable amount of research has been conducted to examine the role of miRNAs in neuropsychiatric disease [147][148][149][150][151][152][153][154][155][156]. We and other investigators have examined the expression of miRNAs in human postmortem brains of depressed subjects, in the brain of animals showing depression-like behavior, and in peripheral tissues such as blood, urine, and saliva [6,96,144,150,[157][158][159][160][161][162][163][164][165][166][167].…”
Section: Studies Of Dna Methylation In Adolescents With Elsmentioning
confidence: 99%
“…Congenital heart diseases are highly prevalent in 22q11.2DS patients, ranging between 22 and 84% depending on patients’ ages [ 33 35 ], suggesting that the downregulation of miR-185 could be involved in the cardiac phenotypes of 22q11.2DS. miR-185 seems to be associated with schizophrenia [ 36 , 37 ], and mouse models suggested that miR-185 is one of the most downregulated miRNAs in schizophrenia-related brain regions [ 26 , 37 , 38 ]. Schizophrenia is also a highly prevalent phenotype on 22q11.2DS, with estimates suggesting that one-third of 22q11.2DS patients will have it in their adulthood [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…miRNA dysregulation has been reported in patients with 22q11.2DS [23][24][25] and SCZ [26,27], but it is unclear how miRNA dysregulation in patients with 22q11.2DS may increase the risk of SCZ [28]. Moreover, miR-185, a miRNA known to be associated with SCZ, is located in the 22q11.2 region and its deletion could dysregulate gene expression and ultimately leading to SCZ [29].…”
Section: Introductionmentioning
confidence: 99%